Scholars and medicine in Sicily between the 18th and 19th centuries Medical knowledge and universal history: Sicilian Medicine - Pareti, Germana (Medicina Historica, 2019)
Inspired by the Enlightenment-era ideal of reconstructing a history of universal knowledge, the 18th and 19th centuries also saw the emergence of universal literary histories in Italy that were dedicated to the totality of humanistic and scientific knowledge. Two scholars – a Sicilian and a Spaniard who had lived a long time in Italy - contributed with monumental works, of which a large part was reserved for Sicilian medicine and the progress thereof. This interest shows the island’s intellectual ebullience and “openness” at the end of the 18th century, not only towards philosophical ideas from beyond the Alps, but also of European medical conceptions which, in many instances – on the island – were reinterpreted and “adapted” to the local culture and needs.